Perspective of using in vitro models to understand immunotherapy-induced cytokine release syndrome - Perkins, Ethan; Cooper, Christopher; Lund, Emma; Alb, Miriam; Morgan, Hannah; Fogal, Birgit; Hewitt, Philip; Mazein, Alexander; Ostaszewski, Marek; Sewald, Katherina (Frontiers in Immunology, 2026)
Since the TGN1412 clinical trial failure to predict cytokine release syndrome (CRS) during preclinical trials, alternative in vitro models have become increasingly important for identifying potential adverse outcomes in early drug development. Considering this, in 2019 the IMI2/EU immune safety avatar (imSAVAR) consortium was established, encompassing academic, industry, and regulatory organizations. ImSAVAR aims to deliver a broad range of tools to enhance our ability to assess the efficacy and safety of immunomodulatory therapies. In addition, imSAVAR uses the adverse outcome pathway (AOP) concept to describe immune-related adverse effects, such as CRS, thereby facilitating the discovery of new biological markers for clinical management and prediction of immune-related adverse effects in nonclinical development. ImSAVAR unanimously agreed that CRS and advanced cytokine release assay (CRA) development is a key focus with regards to immunological safety testing and hazard identification. The CRA field has rapidly accelerated in recent years, with the rise of New Approach Methodologies (NAMs) to provide enhanced predictive immunological safety testing within a clinical setting. Here, we provide an up-to-date review of recent developments of advanced, in vitro CRA models, discuss how these advances may impact the future field of nonclinical toxicology and the understanding of immune-related adverse outcomes and offer guidance on appropriate model selection.